2002
DOI: 10.1002/pd.278
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ultrasound findings and biochemical markers in the second trimester of pregnancy in fetuses with trisomy 21

Abstract: Second trimester ultrasound and biochemical markers are largely independent in fetuses with trisomy 21, however significant correlations between the two were observed in the present series. These may be important in screening protocols that combine second trimester ultrasound and biochemical markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…These are discussed in greater detail below and compared with the results of a similar study by Benn et al 29 These results are also compared with a previous study of fetuses with trisomy 21 by Souter et al 30 In this study, a weakly negative correlation was observed between both FL and HL and hCG. Benn et al 29 observed weakly negative correlations between log hCG and both log BPD/FL and log BPD/HL in control fetuses, but these did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…These are discussed in greater detail below and compared with the results of a similar study by Benn et al 29 These results are also compared with a previous study of fetuses with trisomy 21 by Souter et al 30 In this study, a weakly negative correlation was observed between both FL and HL and hCG. Benn et al 29 observed weakly negative correlations between log hCG and both log BPD/FL and log BPD/HL in control fetuses, but these did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 65%
“…Benn et al 29 observed a significant negative correlation between log AFP and log NF thickness in control pregnancies (correlation coefficient, -0.210; P < .01), which was not apparent in our study. Benn et al also reported a negative correlation between log estriol and log NF thickness (correlation coefficient, -0.032; P < .01) in cases affected with fetal 30 reported a significant positive correlation between NF thickness and hCG among fetuses with trisomy 21 but not in control fetuses. In a comparison of these studies, the possible biochemical correlations with NT are uncertain with the exception of a positive correlation between NT and hCG among fetuses with trisomy 21.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…However, in this age group, it is possible to modify an individual's age-related risk of carrying an aneuploid fetus based on first trimester nuchal translucency measurement, 3 maternal serum markers, [4][5][6] second trimester ultrasound [7][8][9][10][11] or a combination of these methods. [12][13][14][15] Not all older women avail themselves of screening. 16,17 Some do not wish to undergo an invasive test.…”
Section: Introductionmentioning
confidence: 99%